Goal-Directed-Behavior in 22q11.2 Deletion Syndrome: Implication for Social Dysfunctions and the Emergence of Negative Symptoms - Dubourg, Lydia; Maeder, Johanna; Pouillard, Virginie; Eliez, Stephan; Schneider, Maude (Frontiers in Psychiatry, 2020)
Background: Negative symptoms and social dysfunction are core features of the 22q11.2 deletion syndrome (22q11DS). Negative symptoms have been conceptualized as pathology of goal-directed-behaviors. Moreover, goal-directed-behaviors also appear to be a crucial step of social interactions. However, in 22q11DS, the extent to which goal-directed-behavior could be linked to social functioning difficulties and negative symptoms has never been examined. Method: Verbal and non-verbal initiation was measured using the verbal fluency and figural fluency tasks in 93 individuals with 22q11DS and 57 healthy controls aged between 8 and 30 years in order to assess goal-directed-behavior ability. The associations between initiation scores and social functioning/negative symptoms were investigated. Results: Results revealed diminished verbal and non-verbal initiation ability in 22q11DS individuals compared to controls. Initiation deficits appear predictive of social functioning level in 22q11DS. Moreover, a significant association between verbal initiation and negative symptoms severity, especially with social anhedonia, has been observed in 22q11DS participants. Conclusion: Results indicate impaired goal-directed-behavior in the 22q11DS population. These deficits seem to support social functioning impairments frequently observed in the 22q11DS and to a lesser extent the expression of negative symptoms.